Pengaruh Manajemen Operasi di Era Digital Terhadap Penjualan Pada E-Commerce - Hanie Supandi (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
Operations are defined as activities that manage production factors and create value-added products through the transformation process. However, to remain competitive in an increasingly dynamic market, e-commerce companies must optimize their operations, particularly in the areas of logistics, inventory, and customer service management. This is evidenced by the growing ease with which people can meet their needs, especially with the presence of modern marketplaces throughout society. The research method used is literature research, which focuses on the collection and analysis of secondary data from various relevant sources. The sources of information used in this context include books, journal articles, research reports, and other relevant documents. In addition, the collected data will be analyzed systematically to identify patterns, trends, and gaps in previous research. Operational management of e-commerce in Indonesia faces various complex challenges. One of the main issues is related to logistics and delivery. Inadequate infrastructure in various regions, especially remote areas, results in longer delivery times and significantly increased logistics costs. Furthermore, inventory management is also a major issue. Operational management of e-commerce sales encompasses several structural or regulatory aspects, operational aspects, and operational management systems.